Civic identity in the digital age: an investigation into the civic experiences of American young people - Viola, J (2018)
Contemporary society is characterized by digitally mediated interactions and activities, especially through social media. As young people discover their identities, they make decisions about how to present themselves to others, and they develop an understanding of how they fit into society, what it means to be a citizen and to be civically engaged, and how to effectively engage in the political world. Literature reveals the lack of an adequate framework for understanding how young people come to develop their civic identity in contemporary times. This study therefore explores three research questions: 1) In what ways do young people, ages 14 through 17, present themselves to others in contemporary society? 2) What are the mechanisms through which young people form their civic identity in this era, and how do young people understand citizenship and civic engagement? 3) What are the means through which young people engage in the political world, and what factors contribute to this engagement? Using in-depth interviews with 46 participants of diverse backgrounds, this study investigated how young people in the United States aged 14 through 17 conceptualize their civic identities in today’s world. In the United States, the tradition of education for democratic citizenship has declined in recent decades due to a focus on science, technology, engineering, and mathematics (STEM) subjects. Young people have thus not received adequate civic education, and the public has consequently perceived them as disengaged from the political world. Despite this public perception, a growing body of research indicates that young people are civically engaged in non-traditional ways, and there is an assumption that the use of technology among young people will elevate their voices and civic actions. This study finds that while young people are civically engaged, and despite the multitude of digital media that could be used to amplify their voices and causes, they still feel their voices are unheard. These findings highlight certain areas where educators, parents, and policymakers can improve their support for young people’s civic identity formation and feeling that their voices will make a difference. This thesis therefore proposes a new framework for civic identity to reflect the experiences of young people in the digital era, and recommends a reinvigoration of civic education to foster young people’s civic efficacy in contemporary society.